2012
DOI: 10.1186/1471-2458-12-694
|View full text |Cite
|
Sign up to set email alerts
|

Changes in work situation and work ability in young female and male workers. A prospective cohort study

Abstract: BackgroundGood work ability is very important in young workers, but knowledge of work situations that influence work ability in this group is poor. The aim of this study was to assess whether changes in self-reported work factors are associated with self-reported work ability among young female and male workers.MethodsA sample of 1,311 (718 women and 593 men) was selected from a Swedish cohort of workers aged 21–25 years. At baseline and at 1-year follow-up, participants completed a self-administrated question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
2
29
0
4
Order By: Relevance
“…Two studies found that women had an increased risk of musculoskeletal symptoms and aches, pain and numbness, compared to men (Khatun et al, 2004;Korpinen and Paakkonen 2011). Two papers assessed productivity and workability and found no gender difference among young workers (Boström et al, 2008;Boström et al, 2012). Six papers studying mental health among young workers found no gender difference in burnout/exhaustion (Dahlin et al, 2010;Hultell and Gustavsson 2011) suicidal thoughts (Tyssen et al, 2001a), work -related stress (Tyssen et al, 2005) and mental problems (Tyssen et al, 2000;Tyssen et al, 2001b).…”
Section: Summary Of Associationsmentioning
confidence: 99%
“…Two studies found that women had an increased risk of musculoskeletal symptoms and aches, pain and numbness, compared to men (Khatun et al, 2004;Korpinen and Paakkonen 2011). Two papers assessed productivity and workability and found no gender difference among young workers (Boström et al, 2008;Boström et al, 2012). Six papers studying mental health among young workers found no gender difference in burnout/exhaustion (Dahlin et al, 2010;Hultell and Gustavsson 2011) suicidal thoughts (Tyssen et al, 2001a), work -related stress (Tyssen et al, 2005) and mental problems (Tyssen et al, 2000;Tyssen et al, 2001b).…”
Section: Summary Of Associationsmentioning
confidence: 99%
“…These factors enhance the adverse effect of excessive mechanical burden since they increase muscle tension and hinder co-ordination of movements [11,12,13,14,15,16]. Many of those factors are also risk factors for decreased work ability [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of challenging situations that are relevant to workers can lead to decreased production of the individual and a lower capacity to produce solutions for the activities and problems faced in the daily work life 2,32 . Reducing control over work and increasing work demand negative influence on private life were the most important factors associated with reduced work capacity 33 . By associating the sociodemographic and economic variables with the DCM variables, we obtained significant associations with schooling and monthly income.…”
Section: Discussionmentioning
confidence: 99%